Cover Image. Issue 9 (2nd September 2022) - Waldmann, Laura; Leyhr, Jake; Zhang, Hanqing; Allalou, Amin; Öhman‐Mägi, Caroline; Haitina, Tatjana
Abstract : Pectoral fins and shoulder girdles dissected from juvenile zebrafish (wild‐type on the top, gdf5 ‐/‐ on the bottom), with bones colored in blue and cartilage in orange. The gdf5 ‐/‐ fins display a striking absence of proximal radials 2‐4, leaving the posterior lepidotrichia unsupported. From: The role of Gdf5 in the development of the zebrafish fin endoskeleton ; Waldmann L, Leyhr J, Zhang H, Allalou A, Öhman‐Mägi C, Haitina T, Developmental Dynamics . 251(9):1535‐1549. https://doi.org/10.1002/dvdy.399